Analysis of drought hazards in agricultural land in Pacitan Regency, Indonesia - Istika Nita; Aditya Nugraha Putra; Alia Fibrianingtyas (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2020)
Pacitan Regency is a region in East Java Province with varied landforms and high disaster potential, including drought. The drought hazard in this region has not yet been determined. This study was conducted to analyze the potential of drought in Pacitan Regency in 2018 with the previous two decades (1998 and 2008) to predict future droughts. The study also focused on verifying how land-use changes impact drought potential. Mapping drought potential was based on the Ministry of Forestry method and was modified for this study. Drought potential was determined by scoring features and analyzing with a weighted overlay. Reference parameters and patterns of land-use change, as determined by Landsat 5, 7, and 8 satellite imagery, were analyzed. Then, the changing pattern was used to predict future 2030 land-use patterns using business as usual (BAU) analysis. For comparison, a land-use analysis was also done using the land capability class (LCC) and regional spatial plan (RSP). Data was validated using a confusion matrix. The accuracy of the drought estimation for Pacitan Regency was 75%. The results showed that the drought potential high and very-high level risk groups increased. The increase occurred due to changes in land use, specifically land management and plant species selection. Based on the results of the predicting BAU analysis, the level of potential of drought will increase by 2030. The regional spatial plan (RSP) and LCC analysis determined that, with no drought intervention, drought hazard in Pacitan Regency will increase.